Narcotics as a Transnational Organized Crime - Bambang Sunaryo (IHSA Institute, 2021)
The increase in all human activities in various ways, especially in the world of technology and communication makes everything easier and more developed, one aspect that does not escape this convenience is international crime, especially in international drug abuse. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that narcotics abuse is a crime that will greatly impact all aspects of life, the increase in narcotics abuse in Indonesia is caused by an international trade system that has an impact on all lines. life is no exception for those who take advantage of this moment to commit an international crime with their motives and various ways of creating an organization that connects people from various countries, until the most common cases are drug crimes.